Children learning of programming: Learn-Play-Do approach (Latin-American Journal of Computing, 2017)
Writing computer programs is a skill that can beintroduced to children and adolescents since early ages. Althoughchildren can gain skills in coding, there is a lack of motivationand easiness at the time to write logic structures. It raises thequestion, how can children be encouraged to code in a successfulenvironment of learning and fun?. To address this question,this paper shows an experimental approach called ”Learn-Play-Do” for introducing children in the programming. It shows that(1) it is feasible for children to learn about programming byfollowing the proposed approach with (2) encouraging levels oflearning, usefulness content and self-learning programming in(3) a developing country context. The results of an empiricalexperimentation with forty-one children are reported. This workwas implemented as a social project linking the university withthe community.